Higher and bulkier origin of the lumbricals and their clinical relevance. - Sushma RK,; Chandni G,; Bhat KMR, (Department of Surgery, UKM Medical Centre, 2013)
Lumbricals are important small intrinsic muscles of the hand, which arise from the tendons of the flexor digitorum profundus in the palm distal to the flexor retinaculum and are inserted on to the dorsal digital expansion. Variations in the unipinnate/bipinnate pattern of lumbricals, absence of one or more muscles, origin from the superficial flexor tendons and flexor retinaculum have been reported earlier. In the present case, all four lumbricals were arising from the tendons of the flexor digitorum profundus, proximal to the flexor retinaculum in the anterior part of the forearm and extending into the palm through the carpal tunnel. However, there was no variation found with regard to their normal unipinnate (first two) and bipinnate (last two) pattern of origin. In the palm all the four lumbricals were found to be bulkier than their normal size, first one being the bulkiest. The bulky and high origin of lumbricals within the carpal tunnel makes the tunnel a compact space. Therefore, such variation is one of the predisposing factors for the carpal tunnel syndrome. Thus, the knowledge of such variant origin of lumbricals is helpful not only during carpal tunnel release but also during the magnetic resonance imaging (MRI) and ultrasound based diagnosis of carpal tunnel and during the flexor tendon repair and reconstruction.